Immersive Sciences: Engaging Young Minds in Natural Sciences through Virtual and Augmented Reality - Poveda Mora, Ana; Pinilla Arbex, Javier; Ros Magán, Germán (My University, 2024)
.

This study investigated the impact of virtual environments (VEs), such as Virtual Reality (VR) and Augmented Reality (AR), on learning processes within Natural Sciences course of second-grade primary education. To address this objective, an experimental study was designed using a sample of 24 students aged 7 to 8 years from Spain. The subjects used VR and AR to teach about the human body. Knowledge gains were evaluated with pre-tests, post-tests, and delayed tests. Results showed significant improvements in student understanding of the human body. All students improved their results after the experience using VEs, and 14 students achieved post-test scores 80% higher than their pre-test results. The gains obtained through the experience were sustained over time, even after 52 days. While VEs were generally well-received and sparked interest among students in continuing their use, some expressed a preference for traditional learning methods. This research highlights the potential of using VR and AR to overcome challenges in learning abstract or inscrutable concepts in Natural Sciences, such as understanding the internal elements of the human body. By offering immersive experiences, these tools provide a more realistic and tangible view of the subject matter. However, they should be used to complement, not replace, other methodologies, ensuring they align with the student' interests and needs.
Artículos en revistas